Early indicators of fundraising success by venture capital firms - Lahr, Henry; Trombley, Timothy E. (Journal of Corporate Finance, 2020)
We show how a venture capital firm's fundraising is affected by its investment choices. We investigate three leading indicators that are calculated from the types of investments the venture capital firms make: style drift investments, follow-on investments, and investments in which the venture capital firm is not the lead investor in the portfolio company. We find that these investment characteristics are associated with lower fundraising. Characteristics and the reaction of fundraising to characteristics are both moderately stable through time. We also find some evidence that information about investment characteristics is more important for fundraising during bad states of the world and that ex-ante characteristics are related to eventual exit outcomes and financial performance.